Effect of Hyperglycemia on the Total Surface Charge of the Erythrocyte Membrane in Patients with Metabolic Syndrome - V. I. Podzolkov; T. V. Koroleva; M. G. Kudryavtseva (Столичная издательская компания, 2019)
Aim. To study the effect of hyperglycemia on the total surface charge of the erythrocyte membrane (SCEM) in patients with metabolic syndrome (MS).Material and methods. 112 MS patients were examined (45 men and 67 women) (mean age 61.4±7.2 years, average MS duration 8.7±5.2 years). The level of SCEM was determined by adsorption of a positive cationic dye (cationic blue O) on the surface of the plasma membrane of erythrocytes to completely neutralize their negative charge, followed by photometry of the solution and calculation of the number of charges on the cell surface of erythrocytes.Results. In the main group of patients with MS, abdominal obesity was observed in 100% of patients, arterial hypertension - in 73%, hyperglycemia - in 75%, dyslipidemia - in 80%. The level of glycated hemoglobin (HbA1c) was determined in all patients with MS, which was 7.3±1.9%. Patients with MS were conditionally divided according to the level of HbA1c into 2 groups (group 1 - HbA1c from 6.6 to 7.8%, group 2 - more than 7.8%). In MS patients with hyperglycemia, the SCEM values were significantly lower than in the group of patients without hyperglycemia (1.58±0.05×107 and 1.64±0.03×107, respectively; p=0.001)., Significant negative correlations between SCEM and the fasting blood glucose level, hyperglycemia duration, HbA1c level were found in patients with MS.Conclusion. SCEM indices reliably depended on the presence, severity and duration of hyperglycemia, which indicated the effect of impaired carbohydrate metabolism on the state of electric charge of erythrocyte membranes and, therefore, on the mechanisms of microvascular blood flow, thereby contributing to the development of vascular changes in patients with MS.